Тіе Modern treatment of androgenetic alopecia - V. K. Karnaukhov; A. A. Lukyanova; M. I. Lukashina; E. S. Vorobeva; I. M. Afanasov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Androgenetic alopecia (AGA) is the most common reason for hair loss. Its frequency in Caucasian population is up to 80% in men and 42% in women. Current gold standard for AGA treatment includes minoxidil and/or finasteride. Both drugs have moderate treatment efficacy and can cause significant side effects. Minoxidil is the only option for treatment of AGA in women since finasteride has no efficacy. This review considers actual concepts of molecular mechanisms of pathogenesis and current treatment options of AGA with their limitations and shortcomings. Current state and perspectives of novel approaches to AGA treatment, potentially more effective and safe than minoxidil and finasteride, are described. The review discusses growth factors and cytokines, topical 5-alpha-reductase inhibitors, androgen receptor antagonists, prostaglandin analogs and antagonists, Wnt signaling activators and platelet-rich plasma injections.